Synthesis and Characterization of Some New Oxazepines from Triazoles Amines Derivatives - Alkoofee, Wafaa Mahdi; Magtoof , M. S.; Alsaadi, Jamal Harbi Hussein (Journal of Neonatal Surgery, 2025)
In this work, four new Schiff bases and their derivatives (Oxazepine ) were synthesized in two steps. The fiarst step was prepared a new Schiff bases from the reaction of heterocyclic and aromatic aldehyde and amines. The second step included the reaction of prepared Schiff bases derivatives with malic anhydride using few drops of glacial acetic acid as a catalyst to obtain derivatives of seven-membered heterocyclic rings. The newly synthesized compounds 1,3- oxazepine derivatives (a1-a4) were prepared by malic anhydride with new imines (S1-S4).by using microwave at 50W for (2–3 hours).The new derivatives were confirmed by demanding a variety of experimental techniques including 1HNMR and IR